Reply to: “Reflecting the causes of variability of EEG responses elicited by cerebellar TMS” - Po-Yu Fong; Danny Spampinato; Kevin Michell; Marco Mancuso; Katlyn Brown; Jaime Ibáñez; Alessandro Di Santo; Anna Latorre; Kailash Bhatia; John C Rothwell; Lorenzo Rocchi (NeuroImage, 2023)
In their commentary on our recently published paper about electroencephalographic responses induced by cerebellar transcranial magnetic stimulation (Fong et al., 2023), Gassmann and colleagues (Gassmann et al., 2023b) try to explain the differences between our results and their own previous work on the same topic. We agree with them that many of the differences arise from our use of a different magnetic stimulation coil. However, two unresolved questions remain. (1) Which method is most likely to achieve optimal activation of cerebellar output? (2) To what extent are the evoked cerebellar responses contaminated by concomitant sensory input? We highlight the role of careful experimental design and of combining electrophysiological and behavioural data to obtain reliable TMS-EEG data.